2005
DOI: 10.1074/jbc.m504870200
|View full text |Cite
|
Sign up to set email alerts
|

On the Relationships of Substrate Orientation, Hydrogen Abstraction, and Product Stereochemistry in Single and Double Dioxygenations by Soybean Lipoxygenase-1 and Its Ala542Gly Mutant

Abstract: Recent findings associate the control of stereochemistry in lipoxygenase (LOX) catalysis with a conserved active site alanine for S configuration hydroperoxide products, or a corresponding glycine for R stereoconfiguration. To further elucidate the mechanistic basis for this stereocontrol we compared the stereoselectivity of the initiating hydrogen abstraction in soybean LOX-1 and an Ala542Gly mutant that converts linoleic acid to both 13S and 9R configuration hydroperoxide products. Using 11R-3 Hand 11S-3 H-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
111
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 68 publications
(115 citation statements)
references
References 45 publications
4
111
0
Order By: Relevance
“…Perhaps the bulk of the 5-DSA doxyl ring, separated by only three carbons from the carboxylate, interferes with optimal interaction with a base, compared to the situation for 8-, 10-and 12-DSA. However, given the evident hydrophobic effect in binding thermodynamics of DSA molecules, and the fact that esterified fatty acids are good substrates (15,20,29), a specific charge interaction of the polar end of fatty acids with the protein may be relatively unimportant, or dynamic on the EPR time scale (μs to ns), for lipoxygenase substrate/product binding. It is possible that motion of the polar end of a fatty acid between multiple weak binding spots on the surface may assist in driving the hydrocarbon end of the substrate into the non-polar channel and in repositioning the peroxyl radical catalytic intermediate so that it can reoxidize iron.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Perhaps the bulk of the 5-DSA doxyl ring, separated by only three carbons from the carboxylate, interferes with optimal interaction with a base, compared to the situation for 8-, 10-and 12-DSA. However, given the evident hydrophobic effect in binding thermodynamics of DSA molecules, and the fact that esterified fatty acids are good substrates (15,20,29), a specific charge interaction of the polar end of fatty acids with the protein may be relatively unimportant, or dynamic on the EPR time scale (μs to ns), for lipoxygenase substrate/product binding. It is possible that motion of the polar end of a fatty acid between multiple weak binding spots on the surface may assist in driving the hydrocarbon end of the substrate into the non-polar channel and in repositioning the peroxyl radical catalytic intermediate so that it can reoxidize iron.…”
mentioning
confidence: 99%
“…A different category of model places the polar end of substrate near the protein surface, close to one suggested entrance to the cavity in SBL1 between Thr 259 and Leu541 (9). In this arrangement, the hydrophobic end of the substrate lies deeply in the binding pocket (18,20), as shown in Figure 1, essentially in the reverse orientation from that of product in the purple lipoxygenase structure (12). In fact, the stereochemistry of products from double dioxygenations of arachidonic acid demonstrates that substrates can position correctly for catalysis in two orientations: with the methyl end of the substrate chain entering the cavity most deeply or, alternatively, with the carboxyl end entering deepest (20).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…DFT calculations also have revealed that the similar bond formation between the oxygen molecule and the carbon atom of 1,4-pentadiene moiety proceeds in the models of lipoxygenase (Figure 1) for both the Fe(II) (low-spin) and Fe(III) (high-spin) states when the 1,4-pentadiene moiety is deprotonated, and the optimized structure of the resulted ferric state-model containing hydroperoxy-derivative of 1,4-pentadiene is illustrated in Figure 3;this should correspond to a purple Fe III -OOL intermediate observed in SLO (Brash, 1999). As the hydroperoxy-derivative of unsaturated fatty acid has been used to obtain a ferric state lipoxygenase from a ferrous state in vitro (Goffa et al, 2005), it seems quite likely that the oxidation of the ferrous state to a ferric state proceeds through the reaction between the hydroperoxy-derivative formed at the first stage and Fe(II) ion in the native lipoxygenase, and the ferric state lipoxygenase thus formed should play an important role to produce the hydroperoxy-derivatives of fatty acid after the formation of iron(III) lipoxygenase. …”
Section: Resultsmentioning
confidence: 99%